Ultrasound combined with molecular genetics to diagnose hereditary Renpenning syndrome in early pregnancy: a case report - Shen, Yongmei; Zhang, Lei; Li, Yaqi; Yao, Liying; Cao, Jiasong; Lin, Qimei; Nie, Maolin; Wang, Hefei; Wei, Rongxin; Chang, Ying (Frontiers in Genetics, 2025)
Renpenning syndrome is a rare X-linked genetic disorder caused by variants in the PQBP1 gene, but the information about its prenatal presentation is very limited. A 35-year-old woman experienced two male pregnancies with thickened nuchal translucency (NT) (5.5 mm and 5 mm). She went to our prenatal diagnosis center for the current natural conception during the second pregnancy. Trio-whole exome sequencing (TrioWES) of chorionic villus biopsy revealed a 666-bp genetic deletion (chrX:48755195-49760422) in the fetus, inherited from the mother, which included TIMM17B and PQBP1. The couple opted for termination of pregnancy. During the third pregnancy, systematic fetal screening was performed in early pregnancy. An ultrasound examination at 12+1 weeks revealed a thickened NT (6.5 mm), nasal bones abnormalities and a cleft palate. Ultrasound examination at 16 weeks showed ventricular septal defect (VSD), and mild enlargement of the lateral ventricles in the fetus. Chorionic villus biopsy samples were tested for Multiplex Ligation-dependent Probe Amplification (MLPA), showing a 666-bp genetic deletion, inherited from the mother. The couple opted for termination of pregnancy, and the male fetus had a sunken nose and cup-shaped ears leading to a diagnosis of Renpenning syndrome. In conclusion, this emphasized the importance of early systematic pregnancy screening. Increased NT in the first trimester, especially when present in conjunction with ultrasound structural abnormalities such as nasal bone abnormalities, VSD, and mild bilateral ventriculomegaly, emphasized the importance of genetic testing, including chromosome testing, genomic testing, and Whole-exome sequencing.